Unraveling Green Consumer Behaviour: A Systematic Literature Review - Bansah, Pearl Fafa; Gaffar, Vanessa; Disman, Disman; Yeliawati, Ayu Krishna (TIJAB (The International Journal of Applied Business), 2024)
Background: Environmental concerns are increasingly influencing consumer decision-making, and green consumer behaviour has garnered attention in marketing and sustainability. Businesses, governments and researchers must understand green consumer behaviour in order to understand sustainable consumption motives, attitudes, and decisions. Objective: The objectives of this review are to analyse and synthesise how researchers characterise and define green consumer behaviour, examine and evaluate the various research methods used to investigate it, and identify and discuss emerging trends and patterns in green consumer behaviour research. Methods: This review followed the PRISMA standards for systematic literature reviews. A thorough screening procedure was used to select 64 papers from 1633. The EBSCOhost Business Source Ultimate, Science Direct, and Emerald were used. Only English-language research papers published between 2005 and 2023 were included. Articles were found using the "green behaviour,” “consumer behaviour,” “sustainability," and "environmentalism keywords”. Results: Green consumer behaviour was interpreted differently using theories such as the theory of planned behaviour, value-belief-norm theory, social cognitive theory, and environmental identity theory. Modern research in this field examines social media, individual values and motivations, environmental knowledge and awareness, and interventions and marketing strategies for eco-friendly consumption Conclusion: This research illuminates significant findings and current trends in the green consumer behaviour debate. It emphasises the need for precise definitions, rigorous research methods, and further studies on green consumer behaviour dynamics. Businesses, governments, and marketers that promote sustainable consumption can learn from the results. Keywords: Definitions; Green consumer behavior; Research methods; Research trends; Systematic literature review